2020
DOI: 10.1002/ajh.25922
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of late transplant‐associated thrombotic microangiopathy in patients who underwent allogeneic hematopoietic stem cell transplantation

Abstract: Transplant‐associated thrombotic microangiopathy (TA‐TMA) has a wide range of presentations after hematopoietic stem‐cell transplantation (HSCT). We retrospectively studied the risk factors and outcomes of patients with early (≤day 100) and late (>day 100) TA‐TMA. Among the 1451 HSCT recipients, early TA‐TMA occurred in 45 (3.1%) patients at a median of 27 (3‐91) days, and late TA‐TMA in 39 (2.7%) patients at a median of 303 (122‐2595) days. Patients with early TA‐TMA were more likely to have high blood calcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Furthermore, the timing of HSCT-TMA appears different between adult and pediatric patients. HSCT-TMA occurs early after transplantation in pediatric settings (typically within the first 28 days post-transplant), while in a study of adult patients, approximately half of HSCT-TMA events occurred “early” (within 100 days of transplant), and half occurred “late” (after 100 days post-transplant) and were often associated with chronic GvHD or late infections [ 11 , 82 ]. A recent study of adult patients undergoing allogenic HCT showed that HSCT-TMA in the absence of acute GvHD occurs earlier than 100 days, and that comorbid acute GvHD is a key risk factor for late-onset HSCT-TMA in adults [ 83 ].…”
Section: Hsct-tma: Diagnosismentioning
confidence: 99%
“…Furthermore, the timing of HSCT-TMA appears different between adult and pediatric patients. HSCT-TMA occurs early after transplantation in pediatric settings (typically within the first 28 days post-transplant), while in a study of adult patients, approximately half of HSCT-TMA events occurred “early” (within 100 days of transplant), and half occurred “late” (after 100 days post-transplant) and were often associated with chronic GvHD or late infections [ 11 , 82 ]. A recent study of adult patients undergoing allogenic HCT showed that HSCT-TMA in the absence of acute GvHD occurs earlier than 100 days, and that comorbid acute GvHD is a key risk factor for late-onset HSCT-TMA in adults [ 83 ].…”
Section: Hsct-tma: Diagnosismentioning
confidence: 99%
“…In chronic GVHD, the endothelium can be damaged as a result of cytotoxic T-cell-induced injury [14]. Other studies have also shown that many of the immunosuppressive agents used to treat GVHD, such as calcineurin inhibitors and mTOR inhibitors, can cause damage to the endothelium [15,16]. Treatments given following transplant, such as radiation and chemotherapy, are also known to be associated with development of TA-TMA [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…TA-TMA is most often described as an early event in allo-HSCT with a time of onset between 32 and 86 days [ 17 , 18 ], although a recent study by Heybeli et al [ 19 ] documented a bimodal distribution of TA-TMA, with a first peak at day 27 and a second peak around day 200.…”
Section: Incidence Risk Factors and Outcome Of Ta-tmamentioning
confidence: 99%
“…TA-TMA is considered one of the most severe complications of allo-HSCT [ 6 ]. Prognosis is generally poor with a case-fatality varying between 50 and 75% [ 6 , 19 ], underlying the need for early prognostic markers to be defined. The role of renal impairment in predicting lower survival rates has been well documented [ 18 , 20 , 21 ].…”
Section: Incidence Risk Factors and Outcome Of Ta-tmamentioning
confidence: 99%